Identification of a Novel Linear B Cell Epitope on the Sao Protein of Streptococcus suis Serotype 2 - Wang, Jing; Dong, Ruirui; Zou, Ping; Chen, Yuejuan; Li, Na; Wang, Yao; Zhang, Ting; Pan, Xiuzhen (Frontiers in Immunology, 2020)
Surface antigen one (Sao) protein is a bacterial surface protein identified in the important zoonotic pathogen Streptococcus suis 2 (S. suis 2) during an extensive search for functional proteins. The Sao protein is anchored to the bacterial cell wall by the LPVTG motif and is widely distributed in many S. suis serotypes. In this paper, we present the immunodominant epitope peptide of the Sao protein that is recognized by BALB/c antibodies against the Sao protein: 355SEKQMPSVVNENAVTPEKQMTNKENDNIET384 (location Sao355–384). To determine the core epitope recognized by antibodies, we prepared truncation peptide libraries. Analyses of the immunoreactivity of truncation peptides with anti-Sao355–384 serum revealed that the most immunoreactive sequence was 355SEKQMPSVVNENAVTPEK372 (location Sao355–372). Moreover, we observed that this core epitope also showed good specificity based on the ratio of reactivity with serum from S. suis–positive patients compared to serum from S. suis–negative patients. Our results point to the potential of using the Sao355–372 peptide in diagnostic assays to determine S. suis infection in humans.